The impact of a brief mindfulness meditation intervention on cognitive control and error-related performance monitoring - Larson, Michael J.; Steffen, Patrick R.; Primosch, Mark (Frontiers in Human Neuroscience, 2013)
Meditation is associated with positive health behaviors and improved cognitive control. One mechanism for the relationship between meditation and cognitive control is changes in activity of the anterior cingulate cortex-mediated neural pathways. The error-related negativity (ERN) and error positivity (Pe) components of the scalp-recorded event-related potential (ERP) represent cingulate-mediated functions of performance monitoring that may be modulated by mindfulness meditation. We utilized a flanker task, an experimental design, and a brief mindfulness intervention in a sample of 55 healthy non-meditators (n = 28 randomly assigned to the mindfulness group and n = 27 randomly assigned to the control group) to examine autonomic nervous system functions as measured by blood pressure and indices of cognitive control as measured by response times, error rates, post-error slowing, and the ERN and Pe components of the ERP. Systolic blood pressure significantly differentiated groups following the mindfulness intervention and following the flanker task. There were non-significant differences between the mindfulness and control groups for response times, post-error slowing, and error rates on the flanker task. Amplitude and latency of the ERN did not differ between groups; however, amplitude of the Pe was significantly smaller in individuals in the mindfulness group than in the control group. Findings suggest that a brief mindfulness intervention is associated with reduced autonomic arousal and decreased amplitude of the Pe, an ERP associated with error awareness, attention, and motivational salience, but does not alter amplitude of the ERN or behavioral performance. Implications for brief mindfulness interventions and state versus trait affect theories of the ERN are discussed. Future research examining graded levels of mindfulness and tracking error awareness will clarify relationship between mindfulness and performance monitoring.